Fraternity and Biography. (15th September 2017) - Tyssens, Jeffrey
Abstract : For a considerable part of the postwar period, biography did not have a good press at all in historiography: in the 1950s and 1960s vanguard historians usually rejected the format as a typical example of an old fashioned way of writing history, i.e. merely event-related and focussed almost exclusively on great (white) men. Since the 1970s however, microhistory and cultural turn helping, the biographical perspective has gradually returned as a legitimate format of historical research and new reflexive approaches towards its objects, goals and practices have come to the fore. In the history of freemasonry and fraternalism, biographies have been written as well (be it far less in number where non-masonic fraternities are concerned), but epistemological debate about its merits and methods has remained largely absent. This article makes a concise overview of theoretical debates about biography in current historiography and points at innovative approaches of biography writing that can inspire its application to the fraternal field at large.